دور التربية الأسرية في تنمية الوعي البيئي للطفل - دريدي, بنسالم; جويدة مبروك, احمد انور (University of Eloued جامعة الوادي, 2021)
ملخص الدراسة بالعربية: تناولت الدراسة الحالية مشكلة دور الوالدين في توجيه الطفل نحو المحافظة على البيئة وتم اختيار مدينة الرقيبة للدراسة الميدانية، حيث هدفت الدراسة إلى التعرف على دور الوالدين في عملية توجيه الطفل نحو المحافظة على البيئة ،وقد قمنا بوضع الفرضيات التالية في هاته الدراسة :يوجد دور للوالدين في توجيه الطفل نحو المحافظة على البيئة، كذلك تعمل الاسرة بمدينة الرقيبة على تغيير سلوك الاطفال اتجاه البيئة، يوجد دور للمستوى الثقافي للأسرة في ترسيخ قيم ومدركات الاطفال اتجاه البيئة. وقد إعتمدنا في هاته الدراسة على أداة الاستبيان كأداة أساسية والمقابلة كأداة مدعمة للاستبيان، وقد تبنت الدراسة المنهج الوصفي التحليلي الذي يتناسب مع طبيعة موضوع دراستنا وهو الأنسب لهذا النوع من الدراسات وذلك لدى عينة عشوائية بسيطة من مجموعة والدين في مدينة الرقيبة قوامها 60 مفردة، وقد تم إختيارهم بصفة عشوائية . وتم الاعتماد في الاساليب الاحصائية على النسب المئوية و برنامج الحزمة الاحصائية spssمن أجل تحليل الإستبانة، ومعامل الارتباط برسون لصدق الاستبيان وعلى المتوسط الحسابي والانحراف المعياري والوزن النسبي ،وقد أسفرت النتائج النهائية للدراسة على أن للوالدين دور في توجيه الطفل نحو المحافظة على البيئة من خلال مؤشرات عديدة تتبناها الاسر في مدينة الرقيبة الأمر الذي يدعو إلى القول أن للمستوى الثقافي للأسرة دور في ترسيخ قيم ومدركات الاطفال اتجاه البيئة، كما يساهم في تغيير سلوكيات الاطفال اتجاه البيئة ومن هنا يمكن القول أن فرضيات الدراسة قد تحققت. Study summary: The current study dealt with the problem of the role of parents in guiding the child towards preserving the environment، and the city of Al Raqiba was chosen for the field study، where the study aimed to identify the role of parents in the process of guiding the child towards preserving the environment، and we developed the following hypotheses in this study: Orienting the child towards preserving the environment. The family in Al-Raqeeba city also works to change the behavior of children towards the environment. There is a role for the cultural level of the family in consolidating the values and perceptions of children towards the environment. In this study، we have relied on the questionnaire as a basic tool and the interview as a supporting tool for the questionnaire. The study adopted the descriptive analytical approach that suits the nature of the subject of our study and is the most appropriate for this type of studies among a simple random sample of a group of parents in the city of Al-Ruqaiba، consisting of 60 individuals. Choosing them at random. The statistical methods were based on percentages and the statistical package spss program for analyzing the questionnaire، the Person correlation coefficient for the validity of the questionnaire، the arithmetic mean، the standard deviation and the relative weight. It is adopted by families in the city of Al-Raqeeba، which calls for saying that the cultural level of the family plays a role in consolidating the values and perceptions of children towards the environment، and also contributes to changing children’s behavior towards the environment، and from here it can be said that the study’s hypotheses have been achieved.
دراسة ميدانية لعينة من الأسر ببلدية الرقيبة
مذكرة ماستر علم الاجتماع تخصص علم اجتماع التربية
Keywords: التربية الأسرية، الوعي البيئي; Éducation familiale, sensibilisation à l'environnement; Family education, environmental awareness